'I Got to Know Myself Better, My Failings and Faults': Young People's Understandings of being Assessed in Secure Accommodation. (May 2017) - Enell, Sofia
This article explores young people's understandings of assessments conducted in secure accommodation. The concepts of 'institutional identity' and 'text-mediated' actions have been used in the analysis. The main empirical material is repeated interviews with assessed young people during a two-year period. In the findings, the stories of three young people display understandings of appreciation, disappointment and self-development. The assessments seem to have made the youths aware of their 'failings and faults'. An analysis of the written assessments found institutional identities of 'inner problems and unstructured everyday lives'. In conclusion, the young people's understandings of the meanings and implications of the assessments are suggested to be connected to the caseworkers' text-mediated actions and their position in the assessment process. The young people's stories indicate the need to consider the institutional context of the assessments and to acknowledge young people's efforts in care.